2016
DOI: 10.1159/000447878
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgolide B Inhibits Human Bladder Cancer Cell Migration and Invasion Through MicroRNA-223-3p

Abstract: Background/Aims: Ginkgolide B (GB) is currently used as an anticancer drug for treatment of some malignant cancers. However, whether it may have therapeutic effects on bladder cancer remains unknown. Here, we studied the effects of GB on bladder cancer cells. Methods: Bladder cells were treated with different doses of GB, and the effects on ZEB1 and microRNA-223-3p (miR-223-3p) were analyzed by RT-qPCR and/or Western blot. Prediction of a regulatory relationship between miR-93 and 3'-UTR of Beclin-1 mRNA was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 28 publications
(22 reference statements)
2
38
0
Order By: Relevance
“…Many natural products show anti-tumor effects in bladder cancer [33]. The present study indicated that Fcn, an anti-tumor compound, inhibited bladder cancer.…”
Section: Cellular Physiologysupporting
confidence: 57%
“…Many natural products show anti-tumor effects in bladder cancer [33]. The present study indicated that Fcn, an anti-tumor compound, inhibited bladder cancer.…”
Section: Cellular Physiologysupporting
confidence: 57%
“…Although ZNF703 has been shown to play crucial roles in OSCC, the precise molecular mechanisms through which ZNF703 affects proliferation, migration and invasion in oral squamous cell carcinoma remain largely unknown. It is well known that a high proliferative activity of tumour cells is associated with increased cell cycle progression [24-26]. Here, we found that downregulating ZNF703 expression blocked cell growth by suppressing cell cycle progression and repressing the expression of cell cycle G1/S checkpoint factors, including CDK4, CCND1, c-Myc and E2F1.…”
Section: Discussionmentioning
confidence: 56%
“…The effects of Kae on regulating histone deacetylases and non-coding RNAs have been reported [27, 28], which may be closely associated with bladder cancer progression [29, 30]. DNA methylation, as a common epigenetic modification, regulates the expression of genes.…”
Section: Discussionmentioning
confidence: 99%